Hubungan Caring Perawat dengan Kepuasaan Pasien - Ake Langingi (Jurnal Sains & Kesehatan, 2022)
Patient satisfaction can be influenced by the caring behavior of nurses. Nurses who have a concern in providing nursing care to patients in hospitals are nurses who have a caring attitude. The purpose of this study was to analyze the relationship between nurse caring and patient satisfaction at the Komanganaan Health Center UPTD. This type of research is a quantitative research, analytical descriptive with a cross-sectional approach (cross sectional study). The research was carried out at the UPTD Komangana Health Center in June 2021. The results of the study showed that there was a relationship between nurse caring and patient satisfaction at the Komanganan Health Center UPTD. The conclusions of this study : the caring behavior of nurses in UPTD Komangana Health Center was mostly well-behaved; most of the patients at the Komanganan Community Health Center UPTD were satisfied; there is a relationship between caring for nurses and the level of patient satisfaction at the Komanganan Public Health Center UPTD. As a suggestion, this research is used as input for research sites at the Komanganaan Health Center UPTD to further improve health services, especially in caring for every patient who comes for treatment so that the application of basic nursing theory including therapeutic communication can actually be implemented; add knowledge about the basic theories of nursing and community nursing in general:. increase knowledge about the basic theories of nursing and community nursing in general